PATRIMONIAL VIOLENCE: CONCEPTUAL ANALYSIS AND USES OF THE CONCEPT IN BRAZIL, LATIN AMERICA AND FROM A TRANSCULTURAL PERSPECTIVE - da Silva Martins Britto, Bárbara; Flores, Eileen Pfeiffer; Zanello, Valeska (Seven Editora, 2025)
The objectives of this study were (1) to conduct a conceptual analysis of Patrimonial Violence, examining the logic of the concept in articles (from Brazil, Latin America, and Multi-Country) that address the topic. To this end, analytical philosophy tools were employed to reveal distinctions, related concepts, and hidden implications in terminological choices; (2) to investigate its main concepts and uses in Brazil and worldwide. Analyzing the logic of the concept’s use, using analytical philosophy techniques, allowed us to identify structural elements, conceptual boundaries, and forms of patrimonial violence that are often overlooked. This approach highlighted that certain practices, naturalized in contexts of gender inequality, constitute patrimonial violence even when they do not involve the explicit appropriation of material goods. Mapping and analyzing the main uses of the concept in Brazil, Latin America, and from a multi-country cross-cultural perspective indicated that, in Brazil, the concept’s application is restricted to issues of property rights, leaving out important dimensions of this form of violence, confirming what the conceptual analysis had revealed. Furthermore, Latin America is underrepresented in cross-cultural research, suggesting the invisibility of the Global South in academic research. DOI: https://doi.org/10.56238/sevened2025.029-077